Homecoming: rewinding the reductive evolution of the chloroplast genome for increasing crop yields - Llorente, Briardo (2021)
Developing more productive and sustainable crops will be essential to achieving food security in coming decades. A core process in plant evolution has been the transfer of chloroplast-encoded genes to the nuclear genome. We propose reverting this process as a new approach to improve plant disease resistance and photosynthesis in future crops.